1984
DOI: 10.1073/pnas.81.2.471
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand protein binds to extracellular matrices independently of collagen.

Abstract: Platelets contain receptors for vW protein, and monoclonal antibodies against these membrane glycoproteins inhibit the binding of vW protein (9-13). The binding site in the subendothelium has been considered to be collagen, based on vW protein affinity experiments (14, 15) and electron microscopic observations of its proximity to collagen fibers in the subendothelium (16). We have studied the relationship of vW protein and collagen in the extracellular matrix of endothelial cells and of other cells to which vW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
1
2

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 34 publications
7
35
1
2
Order By: Relevance
“…The absence of a preferred order in the adsorption to collagen makes it unlikely that FVIII-VWF binds to collagen via fibronectin, or the reverse. Recent data from endothelial cell culture studies have suggested that a direct interaction occurs between FVIII-VWF and fibronectin because these proteins codistributed in the subendothelial matrix (50). Our data do not rule out such interaction, but they indicate that both FVIII-VWF and fibronectin from plasma interact directly with collagen and are then able to support platelet adhesion.…”
Section: 7±13 (3)contrasting
confidence: 90%
“…The absence of a preferred order in the adsorption to collagen makes it unlikely that FVIII-VWF binds to collagen via fibronectin, or the reverse. Recent data from endothelial cell culture studies have suggested that a direct interaction occurs between FVIII-VWF and fibronectin because these proteins codistributed in the subendothelial matrix (50). Our data do not rule out such interaction, but they indicate that both FVIII-VWF and fibronectin from plasma interact directly with collagen and are then able to support platelet adhesion.…”
Section: 7±13 (3)contrasting
confidence: 90%
“…On the basis of the results presented in this paper and on the basis of previous fluorescence studies (8,15,16), it can be concluded that collagen is not the primary binding site of von Willebrand factor in the vessel wall in the described system.…”
Section: Methodssupporting
confidence: 62%
“…Several groups of investigators have demonstrated that von Willebrand factor binds to collagen types I and III (9)(10)(11)(12)(13)(14), and exposed collagen at the site of vessel injury has been considered to be involved in the binding ofvon Willebrand factor. Recently, Hormia et al and Wagner et al (15,16) have suggested that not collagen but fibronectin may be the binding site of von Willebrand factor.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, vascular subendothelium lacks significant quantities ofthese types of collagen (13)(14)(15). Also, Wagner et al (16) concluded that the subendothelial binding site is not fibrillar collagen, because they found that collagenase digestion oftissue culture-derived subendothelial matrix did not remove vWF. Also, subendothe-1.…”
Section: Introductionmentioning
confidence: 99%